Optimised parallel implementation with dynamic programming technique for the multiple sequence alignment. (10th September 2020) - Gururaj, T.; Siddesh, G.M.
Gene sequencing techniques are very useful in analysing various diseases, especially cancer. The various techniques have been applied for the gene sequence for the effective analysis. These technique help also in reducing the computation time. Most existing methods are of low efficiency in the gene sequence alignment due to lack of proper technique to reduce the gap penalty. In this research, the optimised Needleman-Wunsch (ONW) algorithm is applied for multiple sequence alignment (MSA). The ONW technique uses Needleman-Wunsch (NW) algorithm in parallel implementation for multiple genes. The dynamic programming technique such as the backtracking algorithm is applied for reducing the gap penalty in the gene alignment. The proposed ONW algorithm is applied in the case study and being analysed for its performance. This proves that the proposed ONW algorithm has higher performance compared to the other existing method in the MSA techniques. The proposed method has an average similarity of 88.85%, while the existing method has a similarity of 60.23%.